Insight In The Molecular Structure (spike proteins)/Mechanism of Pathogenesis Against Human Corona Viruses, The Emerging SARS-CoV2 Pandemic; A mini-review - Hussein Ali Hussein Al-Sa'idy,; Dhurgham A.H. Alhasan, (University of Thi-Qar Journal of Science, 2021)
Since the emergence of human type, epidemic corona virus infections SARS-CoV and MERS-CoV outbreaks in addition to the present time SARS-CoV2 outbreaks global researchers and medical specialist efforts are continued mining for specific antiviral agent or vaccine against these rapidly spreading lethal infections. Despite the past and nowadays claims here and there for declaring finding of a feasible and safe coronavirus specific antiviral agent or vaccine arguing between specialists are still ongoing however none of these claimed antiviral agent or vaccine are approved by the FDA. Hence, until now no specific antiviral agent or vaccine are authenticated globally to counteract these seriously hazardous coronavirus outbreaks. Within, the last decade and the past few months after the covid-19 pandemic outbreak through the mining of already known antiviral drugs, clinically used drugs for repurposing and Insilco screening of natural and synthetic compounds are ongoing mission to fasten up the process of drug discovery especially after the current COVID-19 outbreak. However, no rational treatment regimen can be established unless a good understanding of the viral pathogenesis mechanism and the critical biomolecules involved have been considered. Hence, under the urgency of new drug discovery, this survey covers some of the molecular targets antiviral drug intervention strategy against this novel coronavirus.